Benefits of Using ChatGPT in Learning: A Review - Zeswita, Armein Lusi (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
The current state of the world is one where technology significantly negatively impacts everyday life. Objective, this research aims to explain to students the moral principles that must be upheld in their work utilizing the efficiency of Chatbot/ChatGPT technology. The analytical methods used include literature review analysis. The research results show that educators' approaches must be clear and concise. moral knowledge obtained through transformation and creation of an academically oriented culture that is in line with the law and the rules that are strictly followed are based on ethical principles and academic ethics. Moreover, although simple, it was obtained with ChatGPT. However, socially, emotionally, and psychologically, children cannot change. As far as possible, this is due to silent and professional interpersonal interactions, and communications between students and Educators cannot be obtained through ChatGPT media technology. Apart from that, those moral and ethical standards Determining the arithmetic mean is very important in using ChatGPT so that humans can Individual users can clearly understand the potential benefits and impacts This occurs when people are negatively impacted by technology without critical information filtering into their knowledge of the subject.